"Friends" and "Foes" in the Social Space of the Tatar Ethnic Group - Khazieva, Nataliia O.; Khaziev, Aklim Kh.; Klyushina, Elena Vl.; Stepanenko, German N.; Stepanenko, Ravya F. (Journal of History Culture and Art Research, 2017)
The history of the World Culture is a demonstration of the "war" between the two opposites: on the one hand, we see a trend towards unification of all aspects of life on a global scale, and on the other, there is a clear confrontation between different groups of mankind. Of the many causes of the disunity of the people, the authors' focus at the opposition "friend – foe" as a metaphysical principle of formation of social space wasn't chosen by accident. The fact is that any culture, in principle, is dichotomous, and the opposition "friend – foe" is the fullest incarnation of this dichotomy. As a universal principle of the formation and functioning of the cultures, it originally manifests itself in every one of them. And, as the authors of the study suggest: this opposition could either "work" in general on the cross-cultural cooperation and unity or be one of the confrontation sources. The main result of the study is that history has prepared and put forward the Tartars for carrying out a special mission, to unite peoples and cultures. But the revolutionary social upheavals that take place in the modern world pose a threat (in the circumstances of forced migration of peoples, the growth of national consciousness of the former Soviet Union space, and especially in the face of Islamic fundamentalism) on fulfilling this function.